2001
DOI: 10.1034/j.1600-0765.2001.360510.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of matrix metalloproteinase‐1 production by prostaglandin F in human gingival fibroblasts

Abstract: In the present study, we investigated the effect of prostglandin F2alpha (PGF2alpha) and combination of PGF2alpha and interleukin(IL)-1beta on matrix metalloproteinase (MMP)-1 production in human gingival fibroblasts (HGF). PGF2alpha enhanced MMP-1 production in a dose-dependent manner in HGF. Combination of PGF2alpha and IL-1beta induced a synergistic increase of MMP-1 production in HGF. Furthermore, fluprostenol, a specific FP receptor agonist, increased MMP-1 production and induced a synergistic enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…PGF 2a has been shown to induce the differentiation of cementoblasts and stimulate the matrix metalloproteinase activity as well as IL-6 production of gingival fibroblasts (10,11,31). In this study, exposure to PGF 2a stimulates IL-8 production of pulp cells.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…PGF 2a has been shown to induce the differentiation of cementoblasts and stimulate the matrix metalloproteinase activity as well as IL-6 production of gingival fibroblasts (10,11,31). In this study, exposure to PGF 2a stimulates IL-8 production of pulp cells.…”
Section: Discussionmentioning
confidence: 82%
“…Prostaglandin F 2alpha (PGF 2a ) is one of the PG family members that has diverse functions such as mitogenic to fibroblasts and osteoblasts as well as the induction of bone resorption (10,11). PGF 2a might also affect the pathobiologic processes of tissue inflammation and cardiovascular and rheumatic diseases (12).…”
mentioning
confidence: 99%
“…This cytokine probably causes a decrease in the expression of procollagen and an increase in expression of procollagenase, and so could be known as a stimulator for destroying collagen. Noguchi [47] showed that at the presence of phenytoin, the number of IL-1 β receptors increase, by the way, the IL-1β which has been produced by local immune cells has more paracrine attachment.…”
Section: +mentioning
confidence: 99%
“…Interestingly, the FP receptor mRNA expression in GF, buccal mucosa fibroblasts and MG63 cells was identified, but not in GK, SAS tongue cancer epithelial cells and Eahy 926 endothelial cells. Prior reports have detected the expression of FP receptor in GF and MG63 osteoblasts (Noguchi et al. 2001b, Samadfam et al.…”
Section: Discussionmentioning
confidence: 97%